An Analaysis of Students' Anxiety in English Listening at Senior High School of West Sumatera - Nopa liza; Farida Repelita Waty Kembaren (Pendidikan Bahasa Inggris Universitas Nurul Huda, 2022)
Abstract This paper presents the results and analysis of an interview study conducted with English teachers and senior high school students. This research qualitative method and analyzed by narrative inquiry. Participants of this study were 7 students of senior high school of West Sumatera. The instruments used to collect the data by observation and interview, and the questions that used by the researcher to interview the participants are 6. The interview intends to get concrete information about the causes of students' anxiety in English listening, namely; (1) The lack of interest in learning English, (2) The lack of support for students from both inside and outside to learn English, and (3) The lack of students’ vocabulary. This findings have implications for students, so they are able to overcome their anxiety when listening to English, and for teachers can help and give more attention to them in overcoming their anxiety.